Bis(terpyridine) Iron(II) Functionalized Vertically-Oriented Nanostructured Silica Films: Toward Electrochromic Materials - Vilà, Neus; Walcarius, Alain (Frontiers in Chemistry, 2020)
Recent and potential applications of electrochromic materials include smart windows, optoelectronic devices and energy conversion. In this study, we have incorporated bis(terpyridine) iron (II) complexes into vertically-oriented silica thin films deposited on indium-tin oxide (ITO) and their electrochromic behaviour has been investigated. If 2,2':6',2''-terpyridine is commonly used as a ligand for forming metallo-supramolecular assemblies, with the objective to get metal-terpyridine complexes with multiple stable redox states, their simple and reliable arrangement into linear structures enabling effective electronic communication is however more challenging. We propose to overcome this difficulty by generating such complexes within vertical nanochannels on electrode. Terpyridine ligands were firstly immobilized by combining a click chemistry azide/alkyne approach with an electrochemically-assisted self-assembly (EASA) method used to grow an oriented mesoporous silica membrane bearing azide groups which were further derivatized with 4'-ethynyl-terpyridine ligands. The resulting terpyridine-functionalized films were consecutively dipped in an aqueous solution of FeClO4 and then in a solution of terpyridine in acetonitrile to form the bis(terpyridine) iron (II) complexes in situ. The electrochromic properties of the films functionalized at various levels were examined by monitoring the changes in their UV/Vis spectra upon electrochemical oxidation at controlled potential of +1.2 V vs. Ag/AgCl. Due to facile charge delocalization during the Fe 2+ to Fe 3+ redox process, the bis(terpyridine) iron (II) functionalized silica films exhibited electrochromic properties by changing from violet to non-colored using TBABF4 in acetonitrile as an electrolyte. The bis(terpyridine) iron(II) film experienced reversible electrochromic switching by applying +0.5 V in a reverse reduction electrochemical process.